Insecticidal Activity of Some Traditionally Used Ethiopian Medicinal Plants against Sheep Ked Melophagus ovinus. (4th February 2014) - Gemeda, Negero; Mokonnen, Walelegn; Lemma, Hirut; Tadele, Ashenif; Urga, Kelbessa; Addis, Getachew; Debella, Asfaw; Getachew, Mesaye; Teka, Frehiwot; Yirsaw, Kidist; Mudie, Kissi; Gebre, Solomon
Abstract : Twelve medicinal plants and a commercially used drug Ivermectin were examined for insecticidal activity against Melophagus ovinus sheep ked at different time intervals using in vitro adult immersion test. The findings show that at 3.13 µ L/mL, 6.25 µ L/mL and 12.5 µ L/mL concentration of Cymbopogon citratus, Foeniculum vulgare and Eucalyptus globulus essential oils respectively, recorded 100% mortalities against M. ovinus within 3 hour of exposure. Significantly higher insecticidal activity of essential oils was recorded (P = 0.00 ) when compared to 10 μ g/mL Ivermectin after 3-hour exposure of M. ovinus at a concentration of ≥1.57 μ L/mL, ≥3 μ L/mL, and ≥12.7 μ L/mL essential oils of C. citratus, F. vulgare, and E. globulus, respectively. Among essential oils, C. citratus has showed superior potency at a three-hour exposure of the parasite (P = 0.00 ) at a concentration of ≥0.78 μ L/mL. Strong antiparasitic activity was recorded by aqueous extract of Calpurnia aurea (80% mortality) at a concentration of 200 mg/mL within 24 h among aqueous extracts of 9 medicinal plants. The results indicated all the four medicinal plants, particularly those tested essential oils, can be considered as potential candidates for biocontrol of M. ovinus sheep ked.